Cytochrome P450 metabolites of arachidonic acid are elevated in stroke patients compared with healthy controls - Ward, Natalie; Croft, K.; Blacker, D.; Hankey, G.; Barden, A.; Mori, T.; Puddey, I.; Beer, C. (2011)
CYP450AAM [arachidonic acid metabolites of the CYP450 (cytochrome P450) enzyme system] have a range of biological functions. CYP450AAM are involved in the pathogenesis of hypertension, renal function and vascular function, yet their role in stroke has not been clarified. We aimed at determining the levels of circulating CYP450 metabolites in patients with acute ischaemic stroke (<96 h) compared with healthy age- and gender-matched controls. This was a retrospective case-controlled study of 44 acute ischaemic stroke patients and 44 matched controls. A subset of acute ischaemic stroke patients was available for follow-up. Acute ischaemic stroke patients had elevated plasma CYP450AAM, including 20-HETE (20-hydroxyeicosatetraenoic acid) (1921±170 compared with 1108±170 pmol/l, P<0.001), EETs (epoxyeicosatrienoic acids) (77.88±3.34 compared with 35.35±3.34 nmol/l, P<0.0001) and DiHETEs (dihydroxyeicosatetraenoic acids) (92.87±4.61 compared with 68.17±4.61 nmol/l, P<0.0001), as well as increased plasma F2-isoprostane levels (3754±538 compared with 1947±538 pmol/l, P<0.02), the latter a marker of oxidative stress, compared with controls. In a subset analysis of the stroke patients, plasma 20-HETE, EETs and F2-isoprostanes were attenuated 30 days after the stroke. Baseline 20-HETE levels were also associated with lesion size and functional indices within the stroke patients. The present study highlights the elevation in CYP450AAM and oxidative stress in acute ischaemic stroke patients. Further investigation of the effect this has on long-term clinical outcome or whether this can be modified by treatment is warranted.